2017
DOI: 10.1016/j.msec.2016.09.084
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and in vitro evaluation of pH-sensitive magnetic nanocomposites as methotrexate delivery system for targeted cancer therapy

Abstract: This study focuses on the synthesis and in vitro evaluation of magnetic nanocomposites (FeO@LDH) as methotrexate (MTX) delivery system for targeted anticancer therapy. In which, the FeO nanoparticles acted as magnetically responsive carriers; the coating layer of layered double hydroxide (LDH) was used as a storehouse for MTX. The prepared FeO@LDH nanocomposites exhibited a suitable size, good stability and magnetic responsibility (M 36.66emu/g); MTX successfully intercalated into the LDH of FeO@LDH at an entr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 36 publications
(38 reference statements)
1
10
0
Order By: Relevance
“…Hu et al fabricated a novel ultrathin photosensitizer by loading chlorin e6 and carbon dots (CDs) on LDHs, which showed good fluorescent imaging and PDT capabilities, achieving the integration of diagnosis and treatment ( Figure A) . Similarly, Fe 3 O 4 and Au nanoparticles have also been loaded on LDHs with more integrated functions to achieve cancer theranostic applications (Figure B) …”
Section: Layered Double Hydroxide Nanosheetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hu et al fabricated a novel ultrathin photosensitizer by loading chlorin e6 and carbon dots (CDs) on LDHs, which showed good fluorescent imaging and PDT capabilities, achieving the integration of diagnosis and treatment ( Figure A) . Similarly, Fe 3 O 4 and Au nanoparticles have also been loaded on LDHs with more integrated functions to achieve cancer theranostic applications (Figure B) …”
Section: Layered Double Hydroxide Nanosheetsmentioning
confidence: 99%
“…B) pH‐sensitive magnetic nanocomposites (Fe 3 O 4 @LDH) as methotrexate (MTX) delivery system for targeted anticancer therapy. Reproduced with permission . Copyright 2017, Elsevier.…”
Section: Layered Double Hydroxide Nanosheetsmentioning
confidence: 99%
“…Tumor tissue in solid cancers typically exhibit an acidic pH relative to non-cancerous tissue due to the build-up of lactic acid on account of the “Warburg effect” [ 46 ]. This difference in pH has been exploited for tumor tissue targeting by several groups [ 47 , 48 ]. The microenvironment and physical characteristics such as increased interstitial pressure, as well as reduced nutrient and oxygen availability of tumor cells, can be harnessed as potential areas of exploitation by therapeutic methods described previously [ 7 ].…”
Section: Targeted Nanomedicinesmentioning
confidence: 99%
“…A study by Wu et al showed that 84.94% of methotrexate (MTX) was released from Fe 3 O 4 MgAl-LDH (layered double hydroxide) nanoparticles of ~230 nm in the tumor with pH of 3.5 within 48 h. With the dosage of Fe 3 O 4 MgAl-LDH nanoparticles, higher antitumor activity was observed in HUVEC, MCF-7 and HepG2 cell lines [ 47 ]. In order to achieve a controlled release of the drug, research group of Wu J. et al shielded Fe 3 O 4 @SiO 2 -DOX with chitosan (CS) [ 47 ]. These nanoparticles of 63 nm in size released 86.1% of DOX in pH conditions of 4.0 over 48 h where the release profile tracked Higuchi model.…”
Section: Targeting the Tumor Microenvironmentmentioning
confidence: 99%
See 1 more Smart Citation